العزف على آلة البيانو والتعرُّف إلى اتجاھات طلبة المُوسيقا نحوھا في قسمِ العلوم الموسيقية في كلية الفنون الجميلة في جامعة النجاح الوطنية - جاد الله، خليفة (جامعة النجاح الوطنية, 2013)
هدفت الدِّراسة التَّعرُّف إلى العزف على آلة البيانو واتجاهات طلبة المُوسيقا نحوها في قسم العلوم المُوسيقية في كلية الفنون الجميلة في جامعة النجاح الوطنية، ولتحقيق هدف الدراسة استخدم الباحث استبانة مقياس الاتجاهات نحو العزف على آلة البيانو والذي قام بتصميمها وتحكيمها من قبل عدد من المُحكمين في كليَّات الفُنون الجميلة في جامعة اليرموك، والجامعة الأردنية في المملكة الأردنية الهاشمية، وجامعة النجاح الوطنية في فلسطين وتكوَّن المقياس من ثلاثة مجالات وأربعين فقرة من نوع الاختيار من مُتعدِّد، وبعد جمع البيانات عالج الباحث المعلومات باستخدام برنامج الرُّزمة الإحصائية(SPSS) حيث المُتوسطات الحسابية، والنِّسب المئوية، والانحراف المعياري، وأظهرت الدراسة النتائج الآتية: وجود فروق ذلك دلالة إحصائية عند مستوى الدلالة ( = 0.05) بين المتوسطات الحسابية والنسبة المئوية والانحراف المعياري حيث أتى مجال طبيعة المادة وخصائصها بمتوسط (3.95)، وانحراف معياري (0.34)، وهذا يدل على مستوى اتجاهات مرتفع نحو طبيعة المادة وخصائصها، بينما في مجال قيمة المادة وأهميتها أتى بمتوسط (3.96)، وانحراف معياري (0.46)، وهذا يدل على مستوى مرتفع جدا نحو قيمة المادة وأهميتها، وأما في مجال الاستمتاع في المادة فقد أتى بمتوسط (3.97)، وانحراف معياري (0.59)، هذا يدلُّ على مُستوى مُرتفعٍ نحو الاستمتاع في المادَّة، وأوصى الباحث إلى مزيداً من الاهتمام في تدريس آلة البيانو ووضع مساقات أُخرى اختيارية تُعزِّز دراسة الطلبة لها، إذ أنَّ آلة البيانو هي الآلة الأولى في التعامل تربوياً وتهذيبياً في صقل الذَّوق العام لدى الطَّلبة في المدارس والجامعات. This study aimed at knowing the performance of music students in playing the piano instrument and their attitudes towards the instrument it self at the Department of Music Sciences at the College of Fine Arts at An-Najah National UniversitTo achieve the goals of the study, the researcher used a musical attitude scale that he designed to measure the level of music students’ attitudes towards playing the piano instrumenThis scale was assessed by qualified musicians at the Colleges of Fine Arts at Al-Yarmouk University and Jordan University in Jordan, and at An-Najah National University in PalestinThis scale is divided into three domains and forty items of multiple choicIn answering the questions of the study and testing his hypotheses, the researcher employed the (SPSS) by using the following statistical analysis tools: the mean, percentage, and standard deviatioThe results of statistical analyses were as follows: First: There were statistical significant differences at (α = 0,05) between the mean, percentage, and standard deviatioThe benefit of the nature of the subject of music domain, comes out with a mean of (3,95), standard deviation (0,34That means there is a high level of attitude towards the nature of the subjecThe second domain of importance and value of the subject comes out with a mean of (3,95), and standard deviation of (0,46That manes there is a high level of attitude towards that, and the third domain of enjoying the subject, comes out with mean of (3,97), standard deviation of (0,59) that means a high level towards thaIn view of the above results, the researcher recommends to give more attention to teaching playing the piano instrument; he also suggests adding more elective courses to support the same field especially the piano which can also improve the general musical sense of students in schools and universities.
Keywords: طلاب الجامعات -- الفنون الجميلة -- البيانو -- قسم العلوم الموسيقية -- جامعة النجاح الوطنية -- فلسطين -- تنمية المهارات -- الموسيقا